Electrocatalytic reduction of metronidazole using titanocene/Nafion®-modified graphite felt electrode. (10th February 2016) - Saidi, I.; Soutrel, I.; Fourcade, F.; Amrane, A.; Bellakhal, N.; Geneste, F.
Graphical abstract: Abstract: The main objective of this study was to examine the feasibility of an electrocatalytic reduction on titanocene/Nafion ® -modified graphite felt electrode, as pretreatment, before a biological treatment, for the degradation of metronidazole, a nitro biorecalcitrant pollutant. A titanium complex, know as an effective catalyst in the reduction of nitro groups, was immobilized on the electrode surface by encapsulation into a Nafion ® film. The different operating conditions used to prepare the modified electrode, i. e. the initial concentrations of catalyst and Nafion ® and the sonication time, were optimized and the modification of the electrode was highlighted by cyclic voltammetry and electronic scanning microscopy coupled with energy dispersive spectroscopy analysis. The results show a good stability and reproducibility of the modified electrode. Flow heterogeneous catalytic reduction of metronidazole was then carried out with the titanocene/Nafion ® -modified graphite felt as working electrode. The HPLC analysis underlined the total reduction of metronidazole after 1 hour and the evolution of the biological oxygen demand to chemical oxygen demand ratio showed a significant increase of biodegradability from 0.06 before pretreatment to 0.35 ± 0.05 after electrolysis on the modified graphite felt electrode. The comparison of both homogeneous and heterogeneous reactions underlined the interest of the immobilization process that led to a higher stability of the catalyst, giving rise to a higher turnover number and an improvement of biodegradability. The stability of the modified electrode was investigated after electrolysis by cyclic voltammetry and successive electrolyses.